Case Report of Congenital Hepatoblastoma With the Onset at 30-Weeks' Gestation - Yan, Zheng; Bai, Wei; Li, Li; Li, Shuo; Hua, Ying; Zhang, Xiao-xiao; Hou, Xin-lin (Frontiers in Pediatrics, 2022)
This case study reports a hepatoblastoma with onset at 30-weeks’ gestation and rapid growth rate. The postnatal enhanced CT confirmed a intrahepatic mass with a size of 8.5 cm × 6.6 cm and a clear boundary, accompanied by uneven enhancement, displacement, and narrow lumen of the hepatic vein due to compression. The alpha-fetoprotein (AFP) at birth was 1,002,632 ng/ml (normal level 48,406 [±34,718] ng/ml). A diagnosis of congenital hepatoblastoma was established based on the imaging and laboratory outcomes. The infant received chemotherapy of Cisplatin-5fluorouracil-Vincristine (C5V) from the fourth day after birth. After four courses of C5V, a complete tumor resection was performed, and the postoperative pathology was consistent with hepatoblastoma, mixed epithelial and mesenchymal. Four more courses of C5V and one course of C5VD (C5V plus doxorubicin) followed the surgery. Infectious diarrhea and acute kidney injury (stage I) occurred during chemotherapy, which recovered after anti-infection and symptomatic treatment. The patient is currently 2 year old and still in complete remission. In this case, the onset of hepatoblastoma was early, and the tumor grew rapidly resulting in a obvious compression effect. Chemotherapy was started early after birth, and the curative effect was satisfactory, suggesting that the hepatoblastoma based on clinical diagnosis with rapid tumor progression and severe dysfunction of surrounding organs caused by compression should get chemotherapy as soon as possible if pathological diagnosis cannot be obtained temporarily, which also plays an important role in improving the complete resection rate of intraoperative tumor and reducing the recurrence rate of postoperative tumor.